2012
DOI: 10.1007/s10995-012-1019-6
|View full text |Cite
|
Sign up to set email alerts
|

“They Told Me to Come Back”: Women’s Antenatal Care Booking Experience in Inner-City Johannesburg

Abstract: To assess women’s experience of public antenatal care (ANC) services and reasons for late antenatal care attendance in inner-city Johannesburg, South Africa. This cross-sectional study was conducted at three public labour wards in Johannesburg. Interviews were conducted with 208 women who had a live-birth in October 2009. Women were interviewed in the labour wards post-delivery about their ANC experience. Gestational age at first clinic visit was compared to gestational age at booking (ANC service provided). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 20 publications
7
63
1
Order By: Relevance
“…Booking delays are also reported as barriers to early PNC attendance with women in other urban areas of South Africa presenting to clinics early and being told to return much later [13]. This is in contrast with the standard operational policy at clinics in South Africa, where an initial examination including an HIV test is performed when women first present to a clinic because there are no formal appointments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Booking delays are also reported as barriers to early PNC attendance with women in other urban areas of South Africa presenting to clinics early and being told to return much later [13]. This is in contrast with the standard operational policy at clinics in South Africa, where an initial examination including an HIV test is performed when women first present to a clinic because there are no formal appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous barriers to accessing care have been identified, including transportation [10], household commitments [11], under-resourced clinics with excessive waiting lines [11], and a lack of perceived benefit [12], in addition to delayed booking at clinics [13].…”
Section: Introductionmentioning
confidence: 99%
“…The most common barriers to accessing antenatal care are: high indirect costs to pregnant women of attending care,[22,23] antenatal services being at odds with local cultural contexts, overloading of health services with long waiting times, and tainting of health services by previous experiences of being turned away, or abused, by health workers. [2426]. Postpartum care also remains important: nearly three quarters of deaths occurred in the week after childbirth in this study, and in the country as a whole, a high proportion of women who access PMTCT services during pregnancy are not retained postpartum.…”
Section: Discussionmentioning
confidence: 77%
“…Delivery conditions are known to impact women perceived acceptance of delivering within a facility level. 5,[23][24][25][26] Based on these broad concepts of facility based delivery, this study explicitly examined women's perceptions of staff attitudes during delivery sessions, delivery room floor conditions and linings, privacy at delivery rooms, and travel distance/time to facility. Others included hospital arrangements and birth preparedness plans, and intentions for future delivery in a health facility.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The evidence of women shying away from birthing services at the facility due to social and health system barriers are documented. [4][5][6] Furthermore, women acceptance and utilization of facility based birthing services is often characterized by their perceptions of the environmental conditions where these services are provided. One study showed health-provider relational attitudes and clinic environments as important in determining women delivering service utilization levels.…”
Section: Introductionmentioning
confidence: 99%